Tinjauan Literatur: Plastik Antimikrobial Ramah Lingkungan Untuk Kemasan Makanan - Macarius Erwin Yuwono Kristanto; Rahmayetty Rahmayetty; Alia Badra Pitaloka (Peneliti.net, 2023)
Plastic is a material that is widely used for the manufacture of various products. Plastic industrialization continues to be developed to meet human needs but this also has a negative impact. Plastic industrialization produces plastic waste which is a source of environmental damage. Plastic waste that can only decompose in a long time is not friendly and even becomes a threat to environmental sustainability. Departing from these problems, development and research related to plastic products that are able to provide added value but are environmentally friendly are continuously carried out. One example of the development of bioplastics is the research and development of biodegradable plastics for food packaging which contain antimicrobial properties. The application of antimicrobials to biodegradable plastics can be an added value because environmentally friendly plastic packaging can simultaneously maintain and protect food from being easily damaged or spoiled. Various kinds of antimicrobial agents have been studied, especially regarding their respective abilities against bacteria which are a source of food spoilage. This study uses a literature study on bacteria regarding descriptions and explanations and antimicrobial ingredients derived from organic and inorganic materials that are not harmful to health.